A new systemic taxonomy of cyber criminal activity - Babič, Matej; Purković, Damir (2020)
Cybercrime commonly refers to a broad range of different criminal activities that involve computers and information systems, either as primary tools or as primary targets. Cybercrime Science combines the methodology of Crime Science with the technology of Information Security. The few existing taxonomies of Cybercrime provide only general insights into the benefits of information structures; they are neither complete nor elaborated in a systemic manner to provide a proper framework guided by real system-principles. The main problem with such taxonomies is the inability to dynamically upgrade, which is why there is no timely cybersecurity actions. The current and past approaches were based mainly on the technical nature of cyberattacks and such approaches classified the impact of the activities from a criminological perspective. In this article, we present a systemic taxonomy of Cybercrime, based on definitions of the field items and the related data specifications. We develop a new method for estimating the fractal dimension of networks to explore a new taxonomy of Cybercrime activity. This method can serve to dynamically upgrade taxonomy and thus accelerate the prevention of cybercrime.
Bibliografija: str. 26-27.
Abstract.
Keywords: Kibernetički kriminal -- Cyber-kriminal -- Informacijska sigurnost -- Teorija sustava